What is behind the lifestyle risk factors for head and neck cancer? - Iftikhar, Anem; Islam, Mohammad; Shepherd, Simon; Jones, Sarah; Ellis, Ian (Frontiers in Psychology, 2022)
Lifestyle factors are known to be influential determinants of health. According to the World Health Organization (WHO), approximately one third of deaths involve unhealthy lifestyle habits. Amongst lifestyle risk factors for head and neck cancers (HNC), alcohol consumption and smoking have an undeniable role in the multifactorial etiology of the disease. In recent years, the promotion of healthy lifestyle choices has gained significant attention as contributory to improving health and disease prevention. Interventions to tackle these risk factors are vitally important in disease prevention and progression. However, in order to effectively prevent the disease and reduce the risk factors, it is crucial to identify what upstream reasons lead to the adoption of these risk factors in the first place. Stress is a constant aspect of modern-day life and is known to contribute to alcohol and smoking practices. This paper looks at the role of stress and its associated biological pathways as an upstream factor in the adoption of lifestyle risk factors that cause HNC, thus signifying the importance of stress pathways and the Hypothalamus Pituitary Adrenal Axis (HPA) as a locus of interaction between stress, alcohol, smoking and cancer. Despite their widely accepted harmful effects, alcohol and smoking remain deeply rooted in contemporary life. A greater understanding of the impact of stress on lifestyle choices and an exploration of the mechanisms resulting in stress, alcohol and smoking related cancer may highlight opportunities for improved prevention measures through the modification of unhealthy lifestyle choices.